The train wreckers [large type] - Lynch, Sean, active 2013- (The guns of Samuel Pritchard, 2022)
"DEMENTED. DERANGED. DERAILED. 1875. The escalating rivalry between the two major railroad companies takes a dangerous - and deadly - turn when a train is deliberately derailed. Many are killed. More are injured. And Marshal Samuel Pritchard's longtime friend is crippled for life. The mastermind behind the train wreck claims to be the infamous Civil War criminal Jem Rupe, aka "The Trainwrecker of Platte Bridge." There's just one problem: Rupe has been dead for ten years. ... With an oath of vengeance on his lips - and a pair of Colt .45s on his hips - Pritchard sets off to find the trainwrecking fiend, whether it's really Jem Rupe or some copycat maniac. Either way, he'll have to ride the rails with some pretty deranged characters - crooked railroad tycoons, ruthless bounty hunters, trigger-happy gunfighters - before he reaches the end of the line. There's just one way to stop a mass-transit murderer ... and that's dead in his tracks"--